Psychospiritual Dynamics of Repentance: An Islamic Psychological Perspective - Islah, Fadhil Maliky (Asian Journal of Islamic Psychology, 2025)
Repentance is an endeavor to return to one’s primordial nature (fiṭrah) as a servant of Allah, initiated through seeking divine forgiveness and repairing one’s relationship with others. This study examines the multidimensional dynamics of repentance (tawbah) from the perspective of Islamic psychology by integrating theological concepts with contemporary psychological research. A library research design using a narrative review and Conceptual Narrative Analysis was employed to synthesize scholarly sources published between 2016 and 2025, alongside selected classical Islamic texts. The findings indicate that repentance is a dynamic, multilayered process involving intrapersonal, transpersonal, and interpersonal dimensions. The intrapersonal dimension encompasses moral emotions such as guilt, remorse, self-forgiveness, commitment, and spiritual fear. The transpersonal dimension reflects spiritual realignment through increased God-consciousness, ritual worship, and transformative spiritual engagement. The interpersonal dimension manifests in relational repair through apology, reconciliation, and restitution. Together, these dimensions form an integrative model demonstrating that repentance is not a singular act but a sustained psychospiritual transformation restoring the self, the divine connection, and social harmony. This study contributes a theoretically grounded and culturally embedded framework that may inform Islamic psychotherapy, religious counseling, and moral rehabilitation practices.